1,2,3-Triazoles: Controlled Switches in Logic Gate Applications - Debanjana Ghosh; Austin Atkinson; Jaclyn Gibson; Harini Subbaiahgari; Weihua Ming; Clifford Padgett; Karelle S. Aiken; Shainaz M. Landge (Sensors, 2023)
A 1,2,3-triazole-based chemosensor is used for selective switching in logic gate operations through colorimetric and fluorometric response mechanisms. The molecular probe synthesized via “click chemistry” resulted in a non-fluorescent 1,4-diaryl-1,2,3-triazole with a phenol moiety (PTP). However, upon sensing fluoride, it TURNS ON the molecule’s fluorescence. The TURN-OFF order occurs through fluorescence quenching of the sensor when metal ions, e.g., Cu2+, and Zn2+, are added to the PTP-fluoride ensemble. A detailed characterization using Nuclear Magnetic Resonance (NMR) spectroscopy in a sequential titration study substantiated the photophysical characteristics of PTP through UV-Vis absorption and fluorescence profiles. A combination of fluorescence OFF-ON-OFF sequences provides evidence of 1,2,3-triazoles being controlled switches applicable to multimodal logic operations. The “INH” gate was constructed based on the fluorescence output of PTP when the inputs are F− and Zn2+. The “IMP” and “OR” gates were created on the colorimetric output responses using the probe’s absorption with multiple inputs (F− and Zn2+ or Cu2+). The PTP sensor is the best example of the “Write-Read-Erase-Read” mimic.